2021
DOI: 10.1021/acs.orglett.1c02410
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Coelenterazine Degradation Products of Beroe abyssicola Photoprotein Photoinactivation

Abstract: Ca2+-regulated photoproteins of ctenophores lose bioluminescence activity when exposed to visible light. Little is known about the chemical nature of chromophore photoinactivation. Using a total synthesis strategy, we have established the structures of two unusual coelenterazine products, isolated from recombinant berovin of the ctenophore Beroe abyssicola, which are Z/E isomers. We propose that during light irradiation, these derivatives are formed from 2-hydroperoxycoelenterazine via the intermediate 8a-pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…28 The employed theoretical protocol was already used with success in the study of this type of system. [9][10][11][12]22,23,25,26,29,30 ■ RESULTS AND DISCUSSION In this study, we intend to elucidate the chemical details behind the thermolysis and potential chemiexcitation of the two Coelenterazine dioxetane species proposed by both Teranishi et al 21 and Burakova et al, 17 as found in Scheme 1. From now on, these dioxetane species will be termed Clz- Dxt-1 and Clz-Dxt-2, respectively.…”
Section: ■ Computational Detailsmentioning
confidence: 95%
See 4 more Smart Citations
“…28 The employed theoretical protocol was already used with success in the study of this type of system. [9][10][11][12]22,23,25,26,29,30 ■ RESULTS AND DISCUSSION In this study, we intend to elucidate the chemical details behind the thermolysis and potential chemiexcitation of the two Coelenterazine dioxetane species proposed by both Teranishi et al 21 and Burakova et al, 17 as found in Scheme 1. From now on, these dioxetane species will be termed Clz- Dxt-1 and Clz-Dxt-2, respectively.…”
Section: ■ Computational Detailsmentioning
confidence: 95%
“…Furthermore, while dioxetanes are capable of efficient singlet chemiexcitation, 18,19 the study of Burakova et al did not report the thermolysis of Coelenterazine dioxetane as a luminescent pathway. 17 It should be noted that while rare, the study of Burakova et al was not the first to mention a Coelenterazine dioxetane species and its respective thermolysis. 17 In 1996, Teranishi et al studied the chemiluminescent properties of a hydroperoxide derivative of Coelenterazine (Scheme 1) and found that it decomposed via the formation of a dioxetane intermediate (a "mirror" species of that proposed by Burakova et al) but without relevant luminescence.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations